Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.3171/ped.2005.102.2.0167
|View full text |Cite
|
Sign up to set email alerts
|

Is medial temporal injury responsible for pediatric postconcussion syndrome? A prospective controlled study with single-photon emission computerized tomography

Abstract: INOR TBI has been the subject of intense investigation in recent years because it has been increasingly realized that, despite an apparently normal head CT scan, there may be subtle organic brain damage, which may be associated with distressing neuropsychological sequelae. 23 Postconcussion syndrome-including symptoms such as headache, irritability, poor concentration, memory disturbances, dizziness, anxiety, and depression-has been reported to occur in up to 80% of the patients following minor TBI. 8,18 Persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Essentially, SPECT measures regional cerebral blood flow. Some preliminary work in adults with MTBI identified SPECT abnormalities in the medial temporal lobe,25 and a small study on children (ages 2–18) with MTBI suggested that medial temporal hypoperfusion on SPECT was associated with persistent post-concussion syndrome 26. This latter study with children had many scientific limitations, including the lack of clinical data, small numbers, and no neuropsychological assessment.…”
Section: Resultsmentioning
confidence: 97%
“…Essentially, SPECT measures regional cerebral blood flow. Some preliminary work in adults with MTBI identified SPECT abnormalities in the medial temporal lobe,25 and a small study on children (ages 2–18) with MTBI suggested that medial temporal hypoperfusion on SPECT was associated with persistent post-concussion syndrome 26. This latter study with children had many scientific limitations, including the lack of clinical data, small numbers, and no neuropsychological assessment.…”
Section: Resultsmentioning
confidence: 97%
“…A total of 19 longitudinal analyses met all inclusion criteria for the main analysis and included five intervention studies (Table 1; [41]; [46]–[53]). A total of 903 persons were assessed in these studies with NOS scores between 4 to 8.…”
Section: Resultsmentioning
confidence: 99%
“…It may be appropriate to consider MRI in patients with persistent symptoms, although a well‐accepted guideline as to the exact duration of symptoms that warrant such imaging has not yet been defined for the pediatric population. Other nontraditional imaging studies, such as functional MRI and single‐photon emission CT, may prove to have a role in the prediction of concussion severity and time to clinical recovery [28,66].…”
Section: Neuroimagingmentioning
confidence: 99%